2022
DOI: 10.1038/s41563-022-01374-3
|View full text |Cite
|
Sign up to set email alerts
|

A data-science approach to predict the heat capacity of nanoporous materials

Abstract: The heat capacity of a material is a fundamental property that is of significant practical importance. For example, in a carbon capture process, the heat required to regenerate a solid sorbent is directly related to the heat capacity of the material.However, for most materials suitable for carbon capture applications the heat capacity is not known, and thus the standard procedure is to assume the same value for all materials. In this work, we developed a machine-learning approach to accurately predict the heat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 57 publications
0
51
0
Order By: Relevance
“…Fig. 4 compares the outcomes of the PrISMa platform with a constant C p and with the C p obtained from the machine learning model of Moosavi et al [19]. Interestingly, for almost all materials, this gave a lower value of the energy requirements.…”
Section: The Power Of An Integrated Platform For Materials Discoverymentioning
confidence: 89%
See 3 more Smart Citations
“…Fig. 4 compares the outcomes of the PrISMa platform with a constant C p and with the C p obtained from the machine learning model of Moosavi et al [19]. Interestingly, for almost all materials, this gave a lower value of the energy requirements.…”
Section: The Power Of An Integrated Platform For Materials Discoverymentioning
confidence: 89%
“…In addition, capture tests showed that this material outperformed the commercial materials. One of the interesting side-effects of the PrISMa platform is that we screen a little over thousand materials [19]. For these screenings, we used molecular simulations [20] to predict the pure component adsorption isotherms, and we used ideal adsorbed solution theory (IAST) to predict the mixture isotherms.…”
Section: The Power Of An Integrated Platform For Materials Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, machine learning (ML) has emerged as a powerful tool of materials development for analyzing massive amounts of data, predicting physical and chemical properties of materials effectively, and establishing a constructive process–structure–property relationship [ 20 , 21 , 22 , 23 ]. Atwood et al reported that XGBoost is a powerful ML model for predicting the crystallization propensity of metal organic nanocapsules.…”
Section: Introductionmentioning
confidence: 99%